Analysis of Money Circulating in Indonesia during Covid-19 Pandemic - Diana Silaswara; Indra Gunawan; Tjong Se Fung (Fakultas Bisnis, 2020)
The purpose of this analysis is to determine the impact of the Covid-19 pandemic on money circulation in Indonesia. Analysis is seen from the side of money circulating in the community based on Bank Indonesia (BI) data, the policies are taken by the government and the impacts that occur in society as a result of the policies. This research is a descriptive study, because it only observes secondary data obtained from Bank Indonesia since the Covid-19 case began until the end of the study, namely the Bank Indonesia Circulation Money analysis data from December 2019 to April 2020. Then the data is analyzed first combining it with government policy data and data on the impact of Covid-19 on the business world. The results obtained from the analysis conducted are an increase in the money supply and a decrease in electronic money issued by banks. This is due to a decrease in time deposits (Rupiah and Forex), conditions occur because the effect of the number of companies that are doing Termination Employment and pay for employee severance. Government policies by closing shopping centers, the tourism sector and other policies also contribute to create conditions that make people have to convert their time deposits into savings so that they are easy to use if needed.